The Students’s Learning of English Sonnets’ Structures and Sounds - Ariya Jati; Wulandari Retno (Master Program in Linguistics, Diponegoro University, 2020)
This paper describes English sonnets’ structures and sounds discussed in lectures. The scarcity of a practical reference for the study of this distinctive poetic expression in English literature underlies the need for this research. The long-term objective of this research is the availability of a study plan regarding the structures and sounds, with a specific one in the form of teaching material about the English sonnets’ elements. The method used in this study is classroom action research, with the data collecting using classroom observation, and the data processing using qualitative data analysis. The research activities include direct observation of the learning; questionnaire distribution; and data processing. The analysis produces the stages in discussing the sonnets’ structures and sounds. These stages can be developed into a teaching material, which will be useful for the learning of English literature, especially English poetry.